Genome-wide transcriptional profiling of Botrytis cinerea genes targeting plant cell walls during infections of different hosts - Blanco-Ulate, Barbara; Morales-Cruz, Abraham; Amrine, Katherine C. H.; Labavitch, John M.; Powell, Ann L. T.; Cantu, Dario (Frontiers in Plant Science, 2014)
Cell walls are barriers that impair colonization of host tissues, but also are important reservoirs of energy-rich sugars. Growing hyphae of necrotrophic fungal pathogens, such as Botrytis cinerea (Botrytis, henceforth), secrete enzymes that disassemble cell wall polysaccharides. In this work we describe the annotation of 275 putative secreted Carbohydrate-Active enZymes (CAZymes) identified in the Botrytis B05.10 genome. Using RNAseq we determined which Botrytis CAZymes were expressed during infections of lettuce leaves, ripe tomato fruit, and grape berries. On the three hosts, Botrytis expressed a common group of 229 potentially secreted CAZymes, including 28 pectin backbone-modifying enzymes, 21 hemicellulose-modifying proteins, 18 enzymes that might target pectin and hemicellulose side-branches, and 16 enzymes predicted to degrade cellulose. The diversity of the Botrytis CAZymes may be partly responsible for its wide host range. Thirty-six candidate CAZymes with secretion signals were found exclusively when Botrytis interacted with ripe tomato fruit and grape berries. Pectin polysaccharides are notably abundant in grape and tomato cell walls, but lettuce leaf walls have less pectin and are richer in hemicelluloses and cellulose. The results of this study not only suggest that Botrytis targets similar wall polysaccharide networks on fruit and leaves, but also that it may selectively attack host wall polysaccharide substrates depending on the host tissue.